Pengaruh Marketing Mix, Kualitas Pelayanan, dan Citra Merek Terhadap Keputusan Pembelian Konsumen Ayam Geprek (Suatu Kasus Pada Usaha Ayam Geprek di Rumah Chicken) - Meliyana Ayu Putri; Yeni Budiawati; Gugun Gunawan (Universitas Wiralodra, 2026)
A significant decline in sales in culinary businesses is a challenge faced by business actors. One of the causes of this decline is the increasing number of competitors offering similar products. This study aims to determine consumer characteristics and see how the 4P marketing mix, service quality, and brand image influence the purchasing decision for geprek chicken at Rumah Chicken. Data collection techniques used observation, interviews, and questionnaires. The sample used in this study was 100 samples using the accidental sampling technique. The analysis used in this study was instrument testing, classical assumption testing, hypothesis testing, and multiple regression analysis. The results of this study indicate that the variables of product quality (X1) and promotion (X4) partially and simultaneously have a significant effect on the purchasing decision (Y) for geprek chicken at Rumah Chicken. Meanwhile, the variables of price (X2), location (X3), service quality (X5), and brand image (X6) do not affect the purchasing decision (Y) for geprek chicken at Rumah Chicken. It is known that product quality, price, location, promotion, service quality, and brand image influence purchasing decisions by 71.6%, while the remaining 28.4% is explained by other variables not studied.